Peningkatan Kapasitas Mahasiswa Sosiologi UNG dalam Pengembangan Wisata Berkelanjutan di Kota Manado - Sahrain Bumulo; Vanya Dyah Pitaloka M.A.C.; Sainudin Latare; Ridwan Ibrahim; Rudy Harold (JURPIKAT, 2026)
Sustainable tourism requires the integration of environmental, social, and economic dimensions, making the need for human resources who are sensitive to sustainability issues increasingly urgent. As future development analysts and practitioners, students need to be equipped with conceptual understanding and empirical experience so that they are able to comprehensively read the socio-ecological dynamics of a destination. This community service program aims to increase the capacity of Sociology students at Gorontalo State University through expert lectures and field trips. The expert lectures reinforce the theory of sustainable tourism, Community Based Tourism (CBT), and destination carrying capacity. Field visits to Lake Linow were used as an empirical learning strategy to observe ecological conditions, interactions between tourism actors, and sustainability challenges in sensitive natural tourism areas. The results of the activity showed a significant increase in students' understanding, sustainability awareness, and analytical skills in identifying socio-environmental issues. Educational products in the form of infographics reflect their ability to process field findings. This community service contributes to the preparation of human resources capable of supporting sustainable tourism based on knowledge and direct experience.